International courts and the African woman judge : unveiled narratives - Dawuni, Josephine; Kuenyehia, Akua; McDonald, Gabrielle Kirk (New York ; London : Routledge, Taylor & Francis Group, 2018)
"Drawing from postcolonial feminism, feminist institutionalism, feminist legal theory, and legal narratives, this book provides ... narratives of seven women judges that challenge existing discourse on gender diversity in international courts. It answers important questions about how the politics of judicial appointments, gender, geographic location, class, and professional capital combine to shape the lives of women judges who sit on international courts and argues the need to disaggregate gender diversity with a view to understanding intra-group differences"--Provided by the publisher.
Introduction : Challenging gender universalism and unveiling the silenced narratives of the African woman judge / Josephine Jarpa Dawuni -- Women judges in international courts and tribunals : the quest for equal opportunities / Justice Florence Ndepele Mwachande Mumba -- Julia Sebutinde : an unbreakable cloth / Nienke Grossman -- Akua Kuenyehia : leaving a mark along the journey for human rights / Josephine Jarpa Dawuni -- r
Includes bibliographical references and index.
Keywords: Women judges -- Africa, Sub-Saharan.; Women judges -- Africa, Sub-Saharan -- Biography; International courts; International criminal law -- Africa; International criminal law; International courts; Women judges; Africa; Sub-Saharan Africa; Biographies; Biographies